2015
DOI: 10.1021/jm501562a
|View full text |Cite
|
Sign up to set email alerts
|

Nintedanib: From Discovery to the Clinic

Abstract: Nintedanib (BIBF1120) is a potent, oral, small-molecule tyrosine kinase inhibitor, also known as a triple angiokinase inhibitor, inhibiting three major signaling pathways involved in angiogenesis. Nintedanib targets proangiogenic and pro-fibrotic pathways mediated by the VEGFR family, the fibroblast growth factor receptor (FGFR) family, the platelet-derived growth factor receptor (PDGFR) family, as well as Src and Flt-3 kinases. The compound was identified during a lead optimization program for small-molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
192
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(208 citation statements)
references
References 42 publications
1
192
0
4
Order By: Relevance
“…Due to similar pathophysiological processes (inflammation, extracellular matrix proliferation, and angiogenesis) involved in both cancer and chronic disease, an increasing number of anti-cancer agents are being tested for treating chronic respiratory disease and particularly pulmonary disease [25]. For example, the antitumor drugs BIBF1120, SCH-527123, and gefinitib play new roles in the clinical treatment of chronic respiratory disease [27, 31, 56]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to similar pathophysiological processes (inflammation, extracellular matrix proliferation, and angiogenesis) involved in both cancer and chronic disease, an increasing number of anti-cancer agents are being tested for treating chronic respiratory disease and particularly pulmonary disease [25]. For example, the antitumor drugs BIBF1120, SCH-527123, and gefinitib play new roles in the clinical treatment of chronic respiratory disease [27, 31, 56]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, several bioavailable small-molecule agents have been evaluated for their efficacy in a series of respiratory diseases and their complications, including chronic obstructive pulmonary disease (COPD), idiopathic pulmonary fibrosis (IPF), and asthma, etc [25]. For example, recent pharmaceutical and clinical research has demonstrated that BIBF1120, a potent triple blocker of PDGFR, VEGFR, and VEGFR, has significant antitumor efficacy in the treatment of non-small cell lung cancer (NSCLC) [26, 27] and reduces the loss of lung function in IPF [12, 28-30]. Gefinitib, which is also an effective small-molecule agent in NSCLC therapy, plays a new role in asthma treatment via inhibiting airway remodeling and inflammation [31].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of VEGFR2 was a potential mode of action to suppress neoangiogenesis in tumour tissue. Consequently, a lead optimisation programme aimed at the identification of a new chemical entity displaying potent and selective inhibition of VEGFR2 was initiated [1,[4][5][6]. An important target characteristic was selective inhibition of VEGFR2 over other kinases, based on work showing that VEGFR2 is a principal mediator of the physiological and pathological effects of the key endothelial cell mitogen, VEGFA [7].…”
Section: Structure-activity Relationships Of Oxindole Kinase Inhibitomentioning
confidence: 99%
“…Nonclinical pharmacokinetics studies of nintedanib were conducted in CD1 mice, Wistar rats, and cynomolgus and rhesus monkeys (Table 11.6) [6]. Nintedanib exposure was significant in all animals, with moderate variability.…”
Section: Nonclinical Drug Metabolism and Pharmacokineticsmentioning
confidence: 99%
“…Both of these receptors are pro-angiogenic receptor tyrosine kinases and nintedanib was designed as an anti-angiogenic drug for cancer indications [14,15]. Two phase III, international, placebo-controlled, double-blind clinical studies with identical designs (INPULSIS-1 and INPULSIS-2) [9] investigated the efficacy and safety of nintedanib in patients with IPF, after a phase II proof-of-concept study [16].…”
Section: Introductionmentioning
confidence: 99%